Stirling Engine Technology For Parabolic Dish-Stirling System Based On Concentrating Solar Power (CSP) - Liaw, Geok Pheng; Affandi, Rosnani; Ab Ghani, Mohd Ruddin; Gan, Chin Kim; Jano, Zanariah (Trans Tech Publications, 2015)
Solar energy is a renewable energy and can be used as an input source for the heat engines. Stirling engines are mechanical devices working theoretically on the Stirling cycle, in which compressible fluids, such as air, hydrogen, helium, nitrogen or even vapors, are used as working fluids. When comparing with the internal combustion engine, the Stirling engine offers possibility for having high efficiency engine with less exhaust emissions. However, this paper analyzes the basic background of Stirling engine and reviews its existing literature pertaining to dynamic model and control system for parabolic dish-stirling (PD) system.